Variables Affecting Poverty Rate in East Java, Indonesia - Novi Puji Setiyoharti; Teguh Hadi Priyono; Regina Niken Wilantari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study analyzes the qualitative relationship between government fiscal expenditures and poverty reduction in East Java, Indonesia. Despite contributing significantly to national poverty reduction, East Java still has the largest number of poor residents among provinces in Java. The research focuses on four key variables: education expenditure, health expenditure, village funds (Dana Desa), and non-cash food assistance (BPNT). Using a qualitative descriptive approach, the study synthesizes secondary data from 2019 to 2024, including statistical reports from BPS and budget data from the Ministry of Finance, as well as previous empirical studies. Findings reveal that government health expenditure and village funds tend to have a stronger and more consistent impact on reducing poverty, particularly in rural areas. Education spending shows mixed results, often influenced by local capacity and governance. Meanwhile, BPNT contributes to short-term consumption but lacks sustainable poverty alleviation effects due to limited value and targeting issues. The results support the capability approach, highlighting the importance of access to basic services for long-term well-being, and reinforce the social democratic view that structural intervention is necessary to address inequality. This study concludes that poverty reduction efforts must go beyond funding amounts and focus on contextual relevance, implementation quality, and spatial equity. A place-based approach supported by strong local governance is essential for effective poverty alleviation in diverse regions like East Java.